Spatial Organization of Proteasome Aggregates in the Regulation of Proteasome Homeostasis - Karmon, Ofri; Ben Aroya, Shay (Frontiers in Molecular Biosciences, 2020)
Cellular toxicity introduced by protein misfolding threatens cell fitness and viability. Failure to eliminate misfolded polypeptides is associated with various aggregation diseases. In eukaryotes, the ubiquitin proteasome system (UPS) plays a vital role in protein quality control (PQC), by selectively targeting misfolded proteins for degradation. Although ubiquitin-mediated proteasomal degradation of many proteins plays a key role in the PQC system, the proteasome itself can become dysfunctional as a result of transcriptional and translational failures, genomic mutations, or diverse stress conditions, leading to misfolded proteins remaining in every compartment of the cell. Here, we review recent studies that revealed the regulatory pathways that mediate the sorting and elimination of dysfunctional proteasomal subunits. Following inactivation of the 26S proteasome UPS-mediated degradation of its own misassembled subunits is the favored pathway. However, the cytosolic cell-compartment-specific aggregase, Hsp42 mediates an alternative pathway, the accumulation of these subunits in cytoprotective compartments, where they become extensively modified with ubiquitin and are directed by ubiquitin receptors for autophagic clearance (proteaphagy). We also discuss the mechanisms that the cell uses to distinguish between dysfunctional proteasome aggregates and proteasome storage granules (PSGs), reversible assemblies of membrane-free cytoplasmic condensates that form in yeast upon carbon starvation, and help protect proteasomes from autophagic degradation. Regulated proteasome subunit homeostasis is thus controlled through cellular probing of the level of proteasome assembly, and the interplay between UPS-mediated degradation or sorting of misfolded proteins into distinct cellular compartments.